WALLANGAN: Pengembangan Media Pembelajaran Berbasis Gamification Berbantuan Word Wall Materi Pola Bilangan - Kristianti, Lina; Santia, Ika; Hima, Lina Ruhatul (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
The purpose of this study is to develop gamification-based learning media assisted by the word wall platform for technology adaptation and learning tools. This study uses the research and development (RnD) method with the ADDIE model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. The analysis stage is carried out by conducting needs analysis through interviews with teachers and observations; the design stage is carried out by designing Wallangan learning media; the development stage is carried out by producing media and validating; the implementation stage is carried out by testing the media; the evaluation stage is carried out by measuring the validity of the WALLANGAN media. This study was conducted at SMP Negeri 4 Pare, Kediri Regency, East Java. The results of the validity by media experts obtained an average of 86% (very valid), validation by material experts an average of 80% (valid), validation by practitioners an average of 95% (very valid). The WALLANGAN learning media has been declared feasible and valid for use in learning mathematics on number pattern material. Keywords: Research and development, ADDIE, gamification, WALLANGAN